2015
DOI: 10.1093/ckj/sfv074
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic anti-inflammatory pathway activity in dialysis patients: a role for neuroimmunomodulation?

Abstract: BackgroundThe cholinergic anti-inflammatory pathway (CAP) modulates inflammatory responses through the vagus nerve and the α-7-nicotinic acetylcholine receptor (α7nAChR) on macrophages and immune cells. Sympathetic/parasympathetic imbalance and chronic inflammation are both linked to poor outcome in dialysis patients. The aim of this study was to investigate CAP activity in these patients.MethodsTwenty dialysis patients, 12 hemodialysis (HD) and 8 peritoneal dialysis (PD) patients (12 male, 8 female; age range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…This pathway has been investigated in clinical studies of inflammatory diseases. We and others have shown that vagal tone is significantly decreased and associated with inflammatory markers in RA, IBD and dialysis patients [ 127 , 133 , 134 ]. Recent and ongoing research further expands the prospects of modulating the CAP and future therapeutic possibilities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This pathway has been investigated in clinical studies of inflammatory diseases. We and others have shown that vagal tone is significantly decreased and associated with inflammatory markers in RA, IBD and dialysis patients [ 127 , 133 , 134 ]. Recent and ongoing research further expands the prospects of modulating the CAP and future therapeutic possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that dialysis patients have a functional CAP ex vivo [ 127 ]. However, in our pilot VNS study we could not demonstrate significant alterations in cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The whole blood assay, a standard method to test cholinergic function, was performed by a method previously described (Bruchfeld et al, 2010; Hilderman et al, 2015). In brief, whole blood was collected in heparinized tubes and immediately kept in a 37 °C heated container until processed after 60–120 min.…”
Section: Methodsmentioning
confidence: 99%